2011
DOI: 10.1007/s10657-011-9236-9
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary versus enforced tax compliance: empirical evidence for the “slippery slope” framework

Abstract: Taxation, Tax compliance, Power, Trust, Age, Education, H20, H24, H26, G28, K34,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
123
4
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(166 citation statements)
references
References 23 publications
29
123
4
10
Order By: Relevance
“…Second, there may be a role division between power holders and subordinates that is accepted by both parties. In the second scenario, people perceive the authority's power as legitimate, and hence that power is grounded in a shared reality (Kastlunger, Lozza, Kirchler, & Schabmann, 2013;Muehlbacher et al, 2011). The distinction between legitimate and coercive power is arguably relevant for our understanding of tax compliance and, more specifically, our understanding of how power interacts with the procedural justice of the tax authority to shape taxpayers' voluntary compliance.…”
Section: Legitimate and Coercive Power Procedural Justice And Tax Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, there may be a role division between power holders and subordinates that is accepted by both parties. In the second scenario, people perceive the authority's power as legitimate, and hence that power is grounded in a shared reality (Kastlunger, Lozza, Kirchler, & Schabmann, 2013;Muehlbacher et al, 2011). The distinction between legitimate and coercive power is arguably relevant for our understanding of tax compliance and, more specifically, our understanding of how power interacts with the procedural justice of the tax authority to shape taxpayers' voluntary compliance.…”
Section: Legitimate and Coercive Power Procedural Justice And Tax Cmentioning
confidence: 99%
“…First, research has revealed that tax compliance is attributable to a range of factors that are economic or social-psychological in nature (Muehlbacher, Kirchler, & Schwarzenberger, 2011). Yet these various factors are usually studied separately.…”
Section: Introductionmentioning
confidence: 99%
“…According to this framework, "enforced compliance" is mainly affected by the power of the authorities and "voluntary compliance" by the trust in authorities. While a number of studies provide evidence for these hypotheses (Fischer and Schneider 2009, Wahl et al 2010, Mühlbacher et al 2011, it remains still an unsolved question of research, which factors in detail affect both dimensions of tax compliance and what is the relationship among them.…”
Section: Introductionmentioning
confidence: 99%
“…Lisi (2012) has performed a cross-section analysis on the slippery slope framework using data from the World Values Survey, World Bank and International Monetary Fund: the overall analysis underlined the importance and significance of both trust and power in determining overall tax compliance, and trust was found to have more intense positive impact than power. Muehlbacher, Kirchler, & Schwarzenberger (2011) tested SSF on data from the Czech Republic, Austria and the United Kingdom, and confirmed the initial assumptions that trust has a positive impact on voluntary compliance; therefore, if tax authorities seek to implement effective tax policies, they should consider including trust-based measures as a cheap and effective method for inducing tax compliance. Power was found to have positive, but lower impact or was insignificant in explaining tax compliance.…”
Section: Results Of Tax Behaviour Analysis In the European Unionmentioning
confidence: 64%